Public-private partnership as a tool for involving construction enterprises to participate in post-war reconstruction projects of Ukraine - Plys, N.V. (Ways to Improve Construction Efficiency, 2023)
Public-private partnership (PPP) is becoming a key tool in attracting construction companies to participate in construction projects in Ukraine. This form of cooperation between public authorities and the private sector has the potential to implement significant infrastructure facilities that contribute to economic recovery and raising the standard of living of the population. In the context of post-conflict reconstruction, PPPs enable the pool of resources, finance and expertise of the private sector to be mobilized for the rapid and effective recovery of affected areas. Construction companies can make a significant contribution to the reconstruction of infrastructure, housing stock, social and commercial facilities that have been destroyed or damaged as a result of the conflict. PPP creates favorable conditions for investment in construction and reconstruction, ensuring transparency, protection of investors' rights and stability of the conditions for concluding deals. In addition, this mechanism promotes the development of innovative approaches in the construction industry, the introduction of environmentally friendly technologies and the creation of new jobs. Thanks to the implementation of the PPP in the reconstruction process, Ukraine can carry out a quick and high-quality recovery of the economy and infrastructure, contributing to the stabilization of the situation in the affected territories and raising the standard of living of the population. The advantages of public-private partnership in this area are obvious. First, they can pool resources and expertise from both the public and private sectors. Secondly, the PPP promotes the development of competition and the improvement of the quality of work. When competitive conditions are created, the best quality and most efficient solutions are more easily chosen, leading to the improvement of the national infrastructure. In addition, PPP ensures transparency and openness in project implementation. This ends up building the confidence of both investors and the public, which is a factor in the success of large-scale infrastructure projects. After a period of conflict and crisis, building and restoring infrastructure has become a key challenge for Ukraine. This requires large-scale financial and technical resources, which the state cannot always provide. Therefore, the use of public-private partnership (PPP) becomes a strategic step towards restarting the construction and development of infrastructure.